ACE inhibitors potential in correcting vessel wall anti-aggregation activity among patients with arterial hypertension and metabolic syndrome - I. N. Medvedev; I. N. Mezentseva; V. V. Tolmachev (Российский кардиологический журнал)
Captopril and fosinopril potential in correcting vascular wall anti-aggregation activity among patients with arterial hypertension (AH) and metabolic syndrome (MS) has been examined. Sixteen-week fosinopril therapy was associated with vascular wall anti-aggregation activity correction. Captopril therapy did not demonstrate similar effects in the given follow-up period. For body weight reduction, fosinopril treatment should be combined with non-pharmaceutical measures.